2016
DOI: 10.3748/wjg.v22.i13.3652
|View full text |Cite
|
Sign up to set email alerts
|

Dual-input two-compartment pharmacokinetic model of dynamic contrast-enhanced magnetic resonance imaging in hepatocellular carcinoma

Abstract: A dual-input two-compartment pharmacokinetic model (a dual-input extended Tofts model and a dual-input 2CXM) can be used in assessing the microvascular physiopathological properties before the treatment of advanced HCC. The dual-input extended Tofts model may be more stable in measuring the ve; however, the dual-input 2CXM may be more detailed and accurate in measuring microvascular permeability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…Since ktrans only indicates alterations of vascular permeability or blood flow, it seems logical to not be affected by tumor size, as we have also observed [11, 19, 22, 23]. A prior study showed that a higher ktrans value prior to the initiation of sunitinib therapy in advanced HCC is associated with a higher PFS [6].…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Since ktrans only indicates alterations of vascular permeability or blood flow, it seems logical to not be affected by tumor size, as we have also observed [11, 19, 22, 23]. A prior study showed that a higher ktrans value prior to the initiation of sunitinib therapy in advanced HCC is associated with a higher PFS [6].…”
Section: Discussionsupporting
confidence: 53%
“…Furthermore, this technique provides quantitative evaluation of tumor vascular modifications after treatment [2, 6, 11, 16]. One of the parameters obtained by the p-MRI is ktrans, which determines the flow of contrast from the intravascular space to the extracellular space that may indicate a change in tumor blood flow or vascular permeability [8, 11, 19, 23]. …”
Section: Discussionmentioning
confidence: 99%
“…The modified Tofts model was used in postprocessing of DCE‐MRI, with the following equations:Ctfalse(tfalse)=VpCpfalse(tfalse)+Ktransfalse∫0tCp(t)exp)(-KtransVe)(t-tdtKep=KitalictransVewhere C t (t) is the concentration of the agent in the voxel at time t , while C p is the concentration of the agent in the plasma volume. V e is the proportional volume of the extravascular extracellular distribution space (EES).…”
Section: Methodsmentioning
confidence: 99%
“…Chen et al evaluated blood flow in HCC using CT perfusion imaging 7 . Dynamic contrast-enhanced MRI 8 and diffusion MRI imaging 9 have also been used to evaluate blood flow in HCC. Ultrasonography can depict tumor morphology, and the Doppler method can be used to analyze vascularity.…”
Section: Introductionmentioning
confidence: 99%